LMC stars and where to find them: inferring birth radii for external galaxies - Lu, Yuxi; Buck, Tobias; Nidever, David; Ratcliffe, Bridget; Minchev, Ivan; Macciò, Andrea V; Obreja, Aura (Monthly notices of the Royal Astronomical Society, 2024)
It is well known that stars are subject to radial migration, i.e. over time, they move away from their birth location. This dynamical process tends to mix different stellar populations and hence hinders the determination of the true chemical evolution of a galaxy (e.g. metallicity gradients). One way to account for radial migration is to infer stellar birth radii for individual stars. Many attempts to do so have been performed over the last few years, but are limited to the Milky Way, as computing the birth position of stars requires precise measurements of stellar metallicity and age for individual stars that cover large Galactic radii. Fortunately, recent and future surveys will provide numerous opportunities for inferring birth radii for external galaxies such as the LMC. In this paper, we investigate the possibility of doing so using the NIHAO cosmological zoom-in simulations. We find that it is theoretically possible to infer birth radii with a ∼25 per cent median uncertainty for individual stars in galaxies with i) orderliness of the orbits, $\langle v_\phi \rangle /\sigma _{v} > 2 $, ii) a dark matter halo mass greater or equal to approximately the LMC mass (∼2 × 1011 ${\rm M}_\odot$), and iii) after the average azimuthal velocity of the stellar disc reaches ∼70 per cent of its maximum. From our analysis, we conclude that it is possible and useful to infer birth radii for the LMC and other external galaxies that satisfy the above criteria.